Sparkling Surabaya: stakeholder participation in the implementation of a city brand - Indrianto, Agoes Tinus Lis (2019)
Tourism stakeholders are groups of people or individuals with a role, objective and capacity to participate in the city branding process. A city that has the potential to attract visitors can be considered as a destination. Branding of a city can give the city a competitive advantage over the rest. Therefore, a successful city brand requires stakeholders’ participation. This study aims to identify stakeholder participation in urban brand implementation by reviewing the role, level of ownership, key success factors and collaborative platform among stakeholders. The slogan "Sparkling Surabaya" is used as a case study to identify and analyse the participation of stakeholders. Surabaya is chosen despite its industrial characteristics because it has the potential to become a major tourist destination. Qualitative method has been applied through ethnographic and case study approaches which are based on the experience and the participation of the researcher in the process. Data is collected from in-depth interviews, participant observations, focus group discussions and content analysis on documents related to research objectives. The study draws information from 15 informants and other community members representing tourism stakeholders in Surabaya, namely government agencies, private businesses, local residents and visitors. The research framework encompasses culture, people and the city environment. The discussion about destination development depicts the landscape, attractions, events and the local people behavior in the city. Research findings reveal that stakeholder participation in city brands depends on the roles and objectives of the development process. The government shall functions as the regulator while the private business as the executor and the local people as the host, should build good coordination between them to serve local and international visitors. Therefore, the key factors of implementing a city brand are the commitment of all stakeholders, the collaboration among them and the consistency in executing the strategies, especially in promoting the city using a designated brand. This research extends the literature by emphasising the significant role of tourism stakeholders in establishing a city brand. For the industry, this research provides the stakeholders with ideas on the implementation of collaboration platforms to create a successful city brand.